Evaluation of the efficacy and tolerability of 4 mg dienogest in women with adenomyosis and BMI >30 - Manickavasagam, M. Madhubala; Ramalakshmi, M.; Jeyajanani, R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: To evaluate the efficacy and tolerability of 4mg dienogest in women with adenomyosis and BMI >30. Methods: This prospective study, conducted at Lakshmi Madhavan Hospital Pvt Ltd, Tirunelveli, Tamil Nadu, between January and October 2023, included 110 women aged 30-40 years diagnosed with adenomyosis via ultrasonography and presenting with severe dysmenorrhea. These women, all with BMI >30, were administered 4mg Dienogest (2mg twice daily) for eight weeks, followed by a taper to 2mg once daily for 12 weeks. All participants received dietary counselling emphasizing reduced carbohydrate intake and lifestyle modifications. Data on symptom improvement, adverse effects, and adherence were collected and analyzed using STATA 11.0. Results: A significant improvement in symptoms such as menorrhagia, dysmenorrhea, dyspareunia, and chronic pelvic pain was observed in 81% of participants. Adverse effects, including headache (15%), breast discomfort (10%), and mild weight gain (8%), were reported but were well-tolerated. Irregular bleeding led to discontinuation in 3% of cases. Women requiring the 4mg dose beyond eight weeks demonstrated poor adherence to dietary modifications. The overall success rate was 81% (n=89), with a failure rate of 19% (n=21). Conclusion: The study suggests that a higher dosage of Dienogest (4mg) for a limited period is effective and well-tolerated in obese women with adenomyosis who do not respond to the standard 2 mg dose. However, individualized treatment and strict lifestyle adherence are essential for optimal outcomes.